2015
DOI: 10.1261/rna.053918.115
|View full text |Cite
|
Sign up to set email alerts
|

The recruitment of chromatin modifiers by long noncoding RNAs: lessons from PRC2

Abstract: Polycomb repressive complex-2 (PRC2) is a histone methyltransferase required for epigenetic silencing during development and cancer. Among chromatin modifying factors shown to be recruited and regulated by long noncoding RNAs (lncRNAs), PRC2 is one of the most studied. Mammalian PRC2 binds thousands of RNAs in vivo, and it is becoming a model system for the recruitment of chromatin modifying factors by RNA. Yet, well-defined PRC2-binding motifs within target RNAs have been elusive. From the protein side, PRC2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
224
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(240 citation statements)
references
References 150 publications
8
224
0
1
Order By: Relevance
“…The mechanism of aberrant fHC initiation is poorly understood, because human PRC2 does not bind to a specific DNA sequence in the genome (Simon and Kingston 2013). Recent work has shown that PRC2 can be directed by certain long noncoding RNAs (lncRNAs) to key genomic loci regulated by the formation of facultative heterochromatin (Rinn et al 2007;Gupta et al 2010;Margueron and Reinberg 2011;Davidovich and Cech 2015). However, PRC2 also readily binds to the nascent transcripts of actively transcribed genes (Davidovich et al 2013;Kaneko et al 2013), which suggests additional factors are required to regulate the targeted silencing activity of PRC2.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of aberrant fHC initiation is poorly understood, because human PRC2 does not bind to a specific DNA sequence in the genome (Simon and Kingston 2013). Recent work has shown that PRC2 can be directed by certain long noncoding RNAs (lncRNAs) to key genomic loci regulated by the formation of facultative heterochromatin (Rinn et al 2007;Gupta et al 2010;Margueron and Reinberg 2011;Davidovich and Cech 2015). However, PRC2 also readily binds to the nascent transcripts of actively transcribed genes (Davidovich et al 2013;Kaneko et al 2013), which suggests additional factors are required to regulate the targeted silencing activity of PRC2.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly relevant to this discussion are recent observations that long noncoding RNAs (lncRNA) are critical mediators of chromatin structure and gene expression during normal cellular homeostasis and malignant transformation (39). In addition to other highly diverse activities (40), lncRNAs function as scaffolds to recruit DNMTs and histone methyltransferases to chromatin (41), thereby adding another layer of epigenetic regulation in normal cells that is perturbed in malignancies.…”
Section: Review Articlementioning
confidence: 99%
“…Several recent reports suggest that lncRNAs play an important role in gene silencing and PRC2 recruitment to selective loci [22,33,38,[57][58][59][60][61][62][63][64][65][66][67] . For instance, PRC2 and H3K27me3 accumulate on the inactive X chromosome during X inactivation.…”
Section: Introductionmentioning
confidence: 99%